Overview and Research Needs to Achieve Improved Understanding of Earthquake Hazards Affecting the Western Sumatra Coast - Marliyani, Gayatri Indah (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
Natural hazards that are affecting humans are mostly related to geological processes, for example earthquake, volcanic eruption, flooding and landslide. The geological processes itself is a naturally occurring event, it is only become hazardous in the presence of humans as it may cause loss of life and properties. Understanding aspects of geological-related hazards of a region is important to reduce the danger they may pose. Indonesia is located within an active and complicated tectonic setting. Three major tectonic plates: Eurasia, Indo-Australia and Philippine are collide and interact in the vicinity of Indonesia. The mechanism of plate interaction in Indonesia is dominated by subduction, where one plate is subducted beneath the other. The subduction processes are commonly associated with formation of volcanoes as well as active deformation in the crust associated with earthquakes.